Author response to Colle et al. Issue 6 (23rd June 2021) - Fucà, Giovanni; Corti, Francesca; Pietrantonio, Filippo
Abstract : The event of pseudoprogression is rare in patients with MSI-high metastatic colorectal cancer receiving immune checkpoint inhibitors. In this response to the Letter to the Editor by Colle et al, we highlight that the timing of disease re-assessment may influence the incidence of pseudoprogression, with early assessments being associated with higher incidence. Such dynamics should be considered when interpreting the efficacy of treatment.